Creep and Hysteresis Compensation in Pressure-Sensitive Mats for Improving Center-of-Pressure Measurements - Martínez-Cesteros, Javier; Medrano-Sánchez, Carlos; Castellanos-Ramos, Julián; Sánchez-Durán, José Antonio; Plaza-García, Inmaculada; martinez cesteros (IEEE, 2023)
Large-area tactile sensors are used to image the pressure exerted by human body parts. More specifically, they can be used to measure plantar pressure on human stability tests. The center-of-pressure (CoP) trajectory is the primary outcome of such tests. Previous research has shown that the parameters obtained from the trajectory correlate with those obtained from a reference instrument, that is, a force platform (FP). However, there are still noticeable differences. In this work, a low-cost prototype of a pressure- sensitive mat (PSM) has been built and compared with an FP in stability tests. The sensitive material is Velostat, which is readily available. Such a mat could make objective stability tests more accessible. A model of two nonlinear effects, hysteresis and creep, has been considered to compensate for them. Given that it was rather difficult to characterize the large mat with a pneumatic device, a small-sized sensor array was first characterized in a controlled environment. Then the model was extended to the large mat using a suitable scaling factor. The experimental results show that compensating for the nonlinear effects led to a decrease in the differences between the two instruments, the FP and the mat, with an average improvement of 26% in the distance between the trajectories.
Keywords: Tacto; Detectores; Center of pressure (CoP); Creep; Force platform (FP); Hysteresis; Creep; Force platform (FP); Hysteresis; Resistive sensor arrays; Stability test; Tactile sensors